Synthesis and characterization of methoxy poly(ethylene glycol)-b-poly(DL-lactide-co-glycolide-co-ε-caprolactone) di block copolymers: Effects of block lengths and compositions - Baimark Y. (2014)
Methoxy poly(ethylene glycol)-b-poly(D,L-lactide-co-glycolide-co- εcaprolactone) diblock copolymers, designated as MPEG-b-PDLLGCL, with different MPEG block lengths and DLL:G:CL ratios were synthesized via ring-opening polymerization in bulk using MPEG and stannous octoate as the initiating system. The diblock copolymers were characterized using a combination of FT-IR, 1H-NMR, GPC and DSC. The percentage yields of the diblock copolymers were in excess of 90%. 1H-NMR analysis confirmed that the PDLLGCL blocks contained at least some random character. From their DSC curves, the diblock copolymers were amorphous in morphology. Their glass transition temperatures decreased as the MPEG block length increased and as G and CL units were incorporated.